Applying Behavior Change Theories and Qualitative Methods in Substance Misuse Implementation Research: Conceptualizing the Adoption of Breaking Free Online in Real-World Clinical Practice. (June 2017) - Dugdale, Stephanie; Elison, Sarah; Davies, Glyn; Ward, Jonathan
There is insufficient research examining the implementation of complex novel interventions within health care. This may be due to a lack of qualitative research providing subjective insights into these implementation processes. The authors investigate the advantages of applying behavior change theories to conceptualize qualitative data describing the processes of implementation of complex interventions. Breaking Free Online (BFO), a digital treatment intervention for substance misuse, is described as an example of a complex intervention. The authors review previous qualitative research which explored initial diffusion, or spread, of the BFO program, and its subsequent normalization as part of standard treatment for substance misuse within the health and social care charity, "Change, Grow, Live" (CGL). The use of behavior change models to structure qualitative interview findings enabled identification of facilitators and barriers to the use of BFO within CGL. These findings have implications for the development of implementation research in novel health care interventions.